Deteksi Plagiarisme Skripsi Mahasiswa dengan Metode Single-link Clustering dan Jaro-Winkler Distance - Hidayat Abdul Rouf; Ardhi Wijayanto; Abdul Aziz (LPPM Universitas Merdeka Madiun, 2020)
Abstractâ€” The rise of plagiarism is one of the negative impacts of the development of information and communication technology. Plagiarism can occur anywhere. One of the examples is a university with the object of plagiarism as a student's final project. So we need a system to detect plagiarism so that it can suppress plagiarism in the college environment. In detecting the similarity of a writing will be faster if the writing has been grouped before compared to each other. Single-link clustering was chosen because it has a simple algorithm and can be implemented without the initial cluster. In plagiarism plagiarism usually changes the sentence structure so that it looks different Jaro-Winkler distance is chosen because it can detect similarities in paragraphs that have been changed in sentence structure because Jaro-Winkler distance has a flexible indexing with theoretical distance so that a word or character is considered the same. The stages in this study include data collection, preprocessing, grouping writing with Single-link clustering, comparing writing with jaro-winkler distance, and testing with precision and recall. After testing, the average value of precision was 84.37% and recall was 84.37% with a level of plagiarism of 99.1%.Â Keywordsâ€”: jaro-winkler distance; plagiarisme; single-link clustering.